The Dreams of Globalization (Re)produce Banana Republics. Oscar Figueroa as a Critic of Globananalization - Villena Fiengo, Sergio (2021)
This article attempts an approach to the criticism and resistance that develops in the field of visual arts to the neoliberal globalization in which Central America has been inserted for a little over three decades. To this end, a characterization of the subalternized insertion of the region in neoliberal globalization  “Globananalization”) is first carried out, seeking to establish its structural and spectral links with the peripheral modernization and the formation of the so-called banana republic. With this contextual historical basis, the questioning and opposition to the globananalization process that Óscar Figueroa Chávez, a Costa Ricancontemporary artist, has been carrying out for approximately a decade are analyzed.